Optimalisasi Pendapatan Daerah Sektor Mineral Bukan Logam dan Batuan di Kabupaten Karimun Provinsi Kepulauan Riau - Arifah Fitri Rizli (Jurnal Ilmiah Administrasi Pemerintahan Daerah, 2021)
Problem Statement (GAP): The author focuses on problem the lack of optimization in terms of collecting non-metal mineral and rock taxes in Karimun Regency. Purpose: The study aims to know out what local goverments are doing to optimize mineral tax revenues rather then metal and rock taxes in Karimun Regency. Method: This study uses descriptive qualitative research methods with an inductive approach. With the analysis of primary and secondary data obtained through the results of interviews, observations and documentation. Result: Some of the obstacles faced by the Regional Revenue Agency are limited human resources, slow licensing process, the lack of optimal monitoring and supervision, and lack of public awareness. Conclusion: That the collection of tax on non-metallic minerals and rocks in the last few periods has not gone well. This can be seen from the realization of the tax that has not been in accordance with the target. Efforts to optimize the receipt of non-metal mineral and rock taxes and bills by the Regional Revenue Agency are carried out in terms of the certainty and clarity of the Law, the intellectual level of the community, the quality of tax officers, and the tax administration system.